2020
DOI: 10.1021/acs.joc.0c01116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Electron-Deficient Chiral Biphenols and Their Applications in Catalytic Asymmetric Reactions

Abstract: The axially chiral biphenols are known as a broadly applicable chiral source. However, only a few electron-deficient ones have been reported to date. In the present study, chiral biphenols having several electron-withdrawing groups have been designed, and a facile synthetic route from readily available reagents has been developed. Newly synthesized chiral electron-deficient biphenols and biphenol-derived chiral Brønsted acids functioned as effective catalysts for several catalytic asymmetric reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In contrast to expensive chiral separation and difficult scale-up with a chiral HPLC column, herein, (Rac)-1 could be easily separated into optical pure enantiomers in gram scale by the formation of diastereomers with an L-tryptophan derivative and subsequent purification with a common silica column chromatograph. 28 The etherification reactions of the enantiomerically pure (R)-/(S)-1 led to the formation of C1symmetrical imides (R)-/(S)-C1, C2, C3, and C6 and the methylated (R)-/(S)-open (Scheme 1). All obtained compounds were characterized by chiral HPLC analysis, electronic circular dichroism (ECD), 1 H NMR, 13 C NMR, and highresolution mass spectroscopy (Figures S1, S2, and S19−S75, for more synthesis details, see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to expensive chiral separation and difficult scale-up with a chiral HPLC column, herein, (Rac)-1 could be easily separated into optical pure enantiomers in gram scale by the formation of diastereomers with an L-tryptophan derivative and subsequent purification with a common silica column chromatograph. 28 The etherification reactions of the enantiomerically pure (R)-/(S)-1 led to the formation of C1symmetrical imides (R)-/(S)-C1, C2, C3, and C6 and the methylated (R)-/(S)-open (Scheme 1). All obtained compounds were characterized by chiral HPLC analysis, electronic circular dichroism (ECD), 1 H NMR, 13 C NMR, and highresolution mass spectroscopy (Figures S1, S2, and S19−S75, for more synthesis details, see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Demethylation of (Rac)-open with boron tribromide successfully afforded (Rac)-1 in a good yield of 92% (Scheme ). In contrast to expensive chiral separation and difficult scale-up with a chiral HPLC column, herein, (Rac)-1 could be easily separated into optical pure enantiomers in gram scale by the formation of diastereomers with an l -tryptophan derivative and subsequent purification with a common silica column chromatograph . The etherification reactions of the enantiomerically pure (R)-/(S)-1 led to the formation of C1-symmetrical imides (R)-/(S)-C1 , C2 , C3 , and C6 and the methylated (R)-/(S)-open (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that monomers are part of the polymer network, we have recorded the 13 C solid-state CP/MAS NMR spectra of the protected CBPPs-OEt materials (Figure 2a). As can be observed, the chemical shifts at ∼160 to 150 ppm correspond to the C−O bonds in BINOL, and the peaks at 150−110 ppm correspond to the aromatic carbons.…”
Section: Resultsmentioning
confidence: 99%
“…The enantiomeric pure BINOL (1,1′-binaphth-2,2′-diol), its derivatives, and some axially chiral biphenols are important chiral auxiliaries and have been applied in both asymmetric catalysis and chiral recognition. As far as the catalytic behavior of BINOLs is concerned, the enantioselectivity of asymmetric reactions catalyzed by BINOLs depends on the substituents in the different positions of their naphthalene rings. On the other hand, BINOL compounds are moderate Brønsted acids , and only lead to acceptable enantioselectivities on limited reactions. ,, Recently, it has been reported that suitably functionalized BINOL units can be incorporated into porous organic networks that can tailor the chiral properties of molecular catalysts. Chiral fluorescence sensors are a class of materials whose fluorescence emission, in the best scenario, is mainly quenched in the presence of only one analyte’s enantiomer.…”
Section: Introductionmentioning
confidence: 99%
“…Its enantiomer ( S )- L Na‑1 was constructed as well in >99% ee from ( S )- 4e ( ent - 4e ) (Scheme b). Incorporation of the strong electron-withdrawing CF 3 group into chiral ligands currently attracted much attention . From CF 3 -substituted quinoxaline 4i , biarylphosphine oxides 5s and 5t were assembled without obvious racemization and >99% ee was given through a recrystallization in acetonitrile with 67% and 61% yields, respectively.…”
mentioning
confidence: 99%